Control fisicoquímico, en proceso de fabricación de sulfato ferroso - ácido fólico en tabletas recubiertas - Saldaña Delgado, Thalia Verónica (2015)
In this paper the physical and chemical control is performed in the manufacturing process of Ferrous Sulphate - Folic Acid Tablets Coated, Pharmaceutical Laboratory IQFARMA Chemotherapeutic Institute SA. The purpose of this study was to ensure that the results of 40 production batches were within the specifications. Assays were performed in the 3 stages of production of the product: Appearance, humidity and apparent density in the mixing stage; Appearance, average weight, hardness, diameter, friability and disintegration in tableting stage; Aspect trials and average weight and the coating step. The paper concludes that the manufacturing process of Ferrous Sulfate - Folic Acid coated tablets comply with the specifications established by the United States Pharmacopeia (USP 37) and by the Standard Operating Procedure Laboratory work product manufacturer